Pelatihan dan Perancangan Asesmen Autentik Berbasis Kearifan Lokal Cerita Rakyat Melayu Pada Pembelajaran Bahasa Indonesia di SMPN 2 Dumai - Erni; Syofianis Syofianis (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
One form of alternative assessment needed in 21st century learning is authentic assessment. Authentic assessment is an assessment carried out comprehensively to assess starting from the input, process, and output of learning, which includes the domains of attitudes, knowledge, and skills (Wiggens, 1989). Authentic assessments must reflect real-world problems, not the school world. Authentic assessment does not only measure what students know, but emphasizes measuring what students can do. Based on the results of initial observations, it can be explained the problems commonly found related to the use of instruments in learning Indonesian in junior high schools. First, teachers rarely conduct diagnostic tests on students' initial abilities in mastering narrative text material. Second, the teacher still uses traditional text forms in the form of objective questions and does not use authentic material so that students' critical and creative power are low. Third, the lack of debriefing for teachers regarding the application of authentic assessments based on folklore for Indonesian language lessons in junior high schools. For this reason, it is necessary to conduct training and design an authentic assessment based on local wisdom of Malay folklore in Indonesian language learning at SMPN 2 Dumai.